Aconitine promotes ROS-activated P38/MAPK/Nrf2 pathway to inhibit autophagy and promote myocardial injury - Chunai Yang; Jinxiao Fu; Fenshuang Zheng; Yangshan Fu; Xueqiong Duan; Ruiling Zuo; Junbo Zhu (Journal of Cardiothoracic Surgery)
Abstract Background Aconitine has cardiotoxicity, but the mechanism of cardiotoxicity induced by aconitine is limited. The aim of this study was to investigate the mechanism of myocardial injury induced by aconitine. Methods Using aconitine, ROS inhibitor N-acetylcysteine(NAC), the autophagy activitor Rapamycin (Rap) or the P38/MAPK pathway activitor Dehydrocorydaline treats H9C2 cells. CCK-8 assay was used to assay cell proliferation activity. Flow Cytometry was used to detect cell apoptosis. Dichloro-dihydrofluorescein diacetate was used to detect ROS levels. The expression of LC3 was detected by Immunofluorescence Staining. Western blotting detected the expression of related proteins. The mRNA levels of inflammatory factors were detected by RT-qPCR. Results Aconitine inhibits cardiomyocyte proliferation, induces apoptosis and secretion of inflammatory factors. Aconitine activates the P38/MAPK/Nrf2 pathway, induces ROS increase, and promotes autophagy. NAC can inhibit proliferation inhibition, apoptosis, inflammation and P38/MAPK/Nrf2 pathway activation induced by aconitine. Rap and P38 activators can partially recover the effects of NAC on proliferation, apoptosis, inflammation and autophagy of cardiomyocytes. Conclusion Aconitine promotes ROS-activated P38/MAPK/Nrf2 pathway to inhibit autophagy and promote myocardial injury.